Challenges in Detecting Volcanic Forcing in Climate and Societal Proxies: Insights from the 1170/1171 CE Eruption - Ludlow, Francis (My University, 2025)
While our current understanding of the impacts of volcanic eruptions on the atmosphere and climate has significantly advanced, uncertainties persist regarding the climate and societal response to major volcanic events of the Common Era, especially during the high medieval period (1000–1300 CE). This study focuses on a sparsely documented medieval eruption from the late 12th century, considered, on the basis of ice-core evidence, to be one of the most prominent volcanic events of the past millennium. In this context, we explore the challenges researchers may encounter when differentiating between volcanic forcing and internal climate variability in climate and societal proxies. We highlight the importance of accurately dating volcanic eruptions for attribution studies and emphasize the need for a thorough examination of historical sources, along with a deep understanding of prevailing socio-economic and political contexts, when seeking to associate famines, pestilence, or social unrest to the climatic effects of explosive volcanism.
PUBLISHED
Abstract: While our current understanding of the impacts of volcanic eruptions on the atmosphere and climate has significantly advanced, uncertainties persist regarding the climate and societal response to major volcanic events of the Common Era, especially during the high medieval period (10001300 CE). This study focuses on a sparsely documented medieval eruption from the late 12th century, considered, on the basis of ice-core evidence, to be one of the most prominent volcanic events of the past millennium. In this context, we explore the challenges researchers may encounter when differentiating between volcanic forcing and internal climate variability in climate and societal proxies. We highlight the importance of accurately dating volcanic eruptions for attribution studies and emphasize the need for a thorough examination of historical sources, along with a deep understanding of prevailing socio-economic and political contexts, when seeking to associate famines, pestilence, or social unrest to the climatic effects of explosive volcanism.
Keywords: Historical climatology, Paleoclimatology, Volcanism, Ice core, Tree- rings, Historical sources; Making Ireland; Smart & Sustainable Planet; Environment and housing; History